Investigation of potential hybrid renewable energy at various rural areas in Malaysia - Izadyar, N.; Ong, H.C.; Chong, W.T.; Mojumder, J.C.; Leong, K.Y. (Elsevier, 2016)
Feasibility study of the renewable energy resources is usually employed as a primary step in the design of Hybrid Renewable Energy System (HRES), to highlight the most potential sources and the best combinations obtained by using HOMER software. Thus, the main objective of this study is to identify the potential areas in Malaysia utilize solar, the wind and Micro Hydropower (MHP) sources. For this purpose, the results of a study accomplished by Ibrahim Hussein in 2010 are considered to obtain sites with the greatest hydropower potential in Malaysia. Then, a renewable energy resource assessment for these sites was performed to identify the sites that have the greatest solar, wind and hydropower potentials based on total Net Present Cost (NPC) comparison. Based on the historical data, a daily pattern emerged in electricity consumption among rural residents in Malaysia. The results of this study indicate Langkawi is the most potential region for the solar/wind combination by the significant difference with other regions (total NPC of 696,083 USD). After Langkawi, Tioman Islands has the second rank (total NPC of 818,931 USD), while villages in Tioman are the most appropriate sites for installing hybrid renewable energy system with the current specifications. In terms of the premiered locations for solar and hydropower potential, four sites at Lawas in Sarawak and Ranau in Sabah were identified as the greatest potential (total NPC of 354,000 USD). These findings demonstrate that Tioman Islands and Malaysian Borneo Island (Sabah and Sarawak) can be considered as the most attractive regions for the solar/wind/MHP and solar/MHP, respectively.